Is the suburbanisation stage always important in the transformation of large urban agglomerations? The case of the Katowice Conurbation - Krzysztofik, Robert; Kantor-Pietraga, Iwona; Runge, Anna; Spórna, Tomasz (IGiPZ PAN, 2017)
Suburbanisation represents one of the most important contemporary problems facing large urban agglomerations. An analysis of the development of urban agglomerations in Central-Eastern Europe, and especially Poland, leads to the observation that this problem is not particularly advanced in any of them. The aim of this article has thus been to examine how relevant it might be to consider the suburbanisation stage in large Polish agglomerations, as a permanent feature of the Klaassen/Paelinck and van den Berg models. Specifically, the article focuses on Poland’s seven largest agglomerations, though there is a particular emphasis on the Katowice conurbation. The essence of the study lay in the identification of differences in the population balance between these agglomerations, and above all, between their cores and outer zones. The study also included data on the structure characterising out-migrations. A consequence of the study was to draw attention to the apparent diversity of the Katowice conurbation, the only one in Poland to record a population decline in both the core area and the outer zone. This specificity was explained mainly by the drivers of polycentricity and post-industrialism. In other agglomerations, these elements were either absent altogether or were involved in separate shaping of urban regional space.
24 cm
Keywords: suburbanisation; urban agglomeration; postindustrial region; urban polycentrism; Central-Eastern Europe